Interference of silver nanoparticles with essential metal homeostasis in a novel enterohepatic fish in vitro system. Issue 6 (29th May 2019) - Minghetti, Matteo; Schirmer, Kristin
Abstract : Silver nanoparticles induce a similar but attenuated response to ionic silver in an enterohepatic fish in vitro system. Abstract : Silver nanoparticle toxicity has been extensively studied in several vertebrate cells. Its correlation with cellular essential metal homeostasis, however, has largely been overlooked. In this study, we used a novel in vitro model of a fish enterohepatic system to investigate the effect of citrate coated AgNPs (cit-AgNPs) and AgNO3 on the homeostasis of copper, iron and zinc. The intestine and the liver are key tissues for whole body absorption and processing of metals. The enterohepatic system is based on a co-culture of intestinal cells (rainbow trout gut, RTgutGC) grown on permeable supports and hepatic cells (rainbow trout liver, RTL-W1) grown in a sub-located well. We have investigated early responses to sub-toxic and toxic doses of cit-AgNPs and AgNO3 . Viability assays indicated that lysosomes were a target of cit-AgNPs. Moreover, in comparison to AgNO3, cit-AgNPs elicit a similar but attenuated metal stress response (induction of MT mRNA and ATP7A protein trafficking). Metal quantification revealed that, while intestinal cells accumulated similar amounts of silver following non-toxic exposure to equivalent amounts of either AgNO3 or cit-AgNPs, cells exposed to AgNO3 excreted significantly more Ag to the basolateral chamber resulting in higher Ag accumulation in RTL-W1 cells. In addition, application of toxic doses of AgNO3 resulted in a reduction of intracellular zinc and iron. Silver nanoparticles were detected by STEM/EDX in RTgutGC after 3 hours of exposure but not after 24 hours suggesting rapid intracellular dissolution. Thus, Ag is a potent disruptor of essential metal homeostasis and cit-AgNPs, which tend to be more difficult to excrete by the cell, can prolong this effect.